Pengaruh Coping Stress dan College Adjustment terhadap Academic Achievement pada Mahasiswa Unpad Tingkat Pertama - Witsqa Maisa Haq; Achmad Djunaidi; Rasni Adha Yuanita (Provitae: Jurnal Psikologi Pendidikan, 2021)
The aim of this study is to determine the effect of coping stress and college adjustment on academic achievement, of the first-year Unpad students. The approach that used to test the research hypothesis is a quantitative approach with multiple regression analysis techniques. The subjects in this study were 363 Unpad students that still in their first-year research sampling technique uses probability sampling technique with cluster sampling method so that researchers get a sample that can represent the population of Unpad students. Data was obtained through Cope Inventory (Carver, Scheier, and Weintraub, 1989) that have been adapted by Sentani (2016) to measure coping stress, SACQ (Baker & Siryk, 1986) which has been adapted by Hadiana (2016) to measure college adjustment and the GPA score to describe the academic achievement of Unpad students. In this study it was found that coping stress and college adjustment together were proven to have a significant effect on the academic achievement of Unpad first-degree students. The contribution of predictor (R2) coping stress and college adjustment was 5.9%. That is, the effect exerted is small. The dimensions that are proven to have positive effect on student academic achievement are problem focused coping of 6.6%, and academic adjustment of 0,4%. Meanwhile, one dimension is proven to have negative effect on student academic achievement is emotion focused coping of 9,1%.